Minimally invasive postmortem intestinal tissue sampling in malnourished and acutely ill children is feasible and informative - Feutz, E; Voskuijl, W; Finch, PJ; Liu, T-C; Bandsma, RHJ; Tarr, PI; Moxon, CA; VanBuskirk, K; Lawrence, S; Umutesi, G; Tickell, KD; Berkley, JA; et al. (Oxford University Press, 2021)
BACKGROUND:Intestinal disorders such as environmental enteric dysfunction (EED) are prevalent in low- and middle-income countries (LMICs) and important contributors to childhood undernutrition and mortality. Autopsies are rarely performed in LMICs but minimally invasive tissue sampling is increasingly deployed as a more feasible and acceptable procedure, although protocols have been devoid of intestinal sampling to date. We sought to determine (1) the feasibility of postmortem intestinal sampling, (2) whether autolysis precludes enteric biopsies' utility, and (3) histopathologic features among children who died during hospitalization with acute illness or undernutrition. METHODS:Transabdominal needle and endoscopic forceps upper and lower intestinal sampling were conducted among children aged 1 week to 59 months who died while hospitalized in Blantyre, Malawi. Autolysis ratings were determined for each hematoxylin and eosin slide, and upper and lower intestinal scoring systems were adapted to assess histopathologic features and their severity. RESULTS:Endoscopic and transabdominal sampling procedures were attempted in 28 and 14 cases, respectively, with >90% success obtaining targeted tissue. Varying degrees of autolysis were present in all samples and precluded histopathologic scoring of 6% of 122 biopsies. Greater autolysis in duodenal samples was seen with longer postmortem interval (Beta = 0.06, 95% confidence interval, 0.02-0.11). Histopathologic features identified included duodenal Paneth and goblet cell depletion. Acute inflammation was absent but chronic inflammation was prevalent in both upper and lower enteric samples. Severe chronic rectal inflammation was identified in children as young as 5.5 weeks. CONCLUSIONS:Minimally invasive postmortem intestinal sampling is feasible and identifies histopathology that can inform mortality contributors.